Introduction to Systems Biology - Choi, Sangdun (Humana Press : Imprint: Humana, 2007)
Introduction to Systems Biology is an introductory text for undergraduate and graduate students who are interested in comprehensive biological systems. The authors provide a broad overview of the field using key examples and typical approaches to experimental design. The volume begins with an introduction to systems biology and then details experimental omics tools. Other sections introduce the reader to challenging computational approaches to help understand biological dynamic systems. The final sections of the volume provide ideas for theoretical and modeling optimization in systemic biological researches, presenting most algorithms as implementations, including an up-to-date full range of bioinformatic programs and available successful applications. Informative and cutting-edge, this volume presents a clear and intuitive illustration of the biological systemic approaches and introduces ideal computational methods for research. Introduction to Systems Biology is an indispensable resource, providing a first glimpse into the state-of-the-art in systems biology.